VviAPRT3 and VviFSEX: Two Genes Involved in Sex Specification Able to Distinguish Different Flower Types in Vitis - Coito, João L.; Ramos, Miguel J. N.; Cunha, Jorge; Silva, Helena G.; Amâncio, Sara; Costa, Maria M. R.; Rocheta, Margarida (Frontiers in Plant Science, 2017)
Vitis vinifera vinifera is a hermaphrodite subspecies, while its ancestor, Vitis vinifera sylvestris, is dioecious. We have identified two genes that together allow the discrimination between male, female and hermaphrodite Vitis plants. The sex locus region on chromosome 2 was screened resulting in the discovery of a new gene, VviFSEX. The same screening revealed another gene, VviAPRT3, located in the sex region, that be used as a sex marker. Both genes are good candidates to be involved in flower sex differentiation in grapevine. To assess their role in sex specification, spatial and temporal expression analysis was performed. The expression of VviFSEX is detected in petals, stamens and carpel primordia of all flower types, making its putative function unclear; however, female plants display a single allele for this gene, while male and hermaphrodites display two alleles. On the other hand, the specific expression of VviAPRT3 in the carpel primordial of male plants suggests a possible role in the abortion of pistil structures. We propose a model to explain the carpel abortion in male flowers and the absence of stamen viability in female flowers. In addition, this work reinforces the presence of a sex locus on Vitis chromosome 2.